Students’ Motivation on Using RuangGuru as Digital Platform in Leaning English - Fauzia Sehuddin; Fatimah Hidahyani Amin; Samtidar Samtidar (ELT Worldwide: Journal of English Language Teaching, 2022)
The rapid development of digital technology has changed conventional systems into modern systems, resulting in new products, systems, and platforms that can be more useful for everyone. Likewise, in the field of education, the development of E-Learning can improve the quality of learning or learning media to be more innovative and interactive. One of the most recently established and popular E-learning media is Ruangguru. Ruangguru as a digital platform in industry 4.0 can motivate students to learn English and get a positive response from students. This research examines students' motivation toward Ruangguru as a digital platform for learning English. This research was conducted using survey research, covering both quantitative and qualitative data. Data was collected using questionnaires and interviews. The findings of this study indicate that Ruangguru can motivate students in learning English.